2013
DOI: 10.1002/pmic.201300442
|View full text |Cite
|
Sign up to set email alerts
|

Back to the future-The value of single protein species investigations

Abstract: In proteomics, in the past years, there was a focus on high throughput and reaching of large numbers of identified proteins with the basic discourse of protein expression. To avoid the impression of producing pure lists attempts are usually made to correlate proteins changed in amount between two biological situations to different pathways or protein interactions. This discourse is based on two simplifications, which limit the applicability of proteomics drastically: (i) it is sufficient to quantify a protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Due to a dysregulation of the fine-tuned protein processing machinery or pathological effects such as oxidative stress, proteins are modified, potentially leading to harmful protein species [4] , [5] , [6] , [7] . Therefore, to better understand disease-related proteomes on a functional level, tissue proteome must be analyzed with respect to protein species [8] , [9] , [10] . In the past decade, significant progress has been made in the field of proteomics that have now made protein species accessible to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a dysregulation of the fine-tuned protein processing machinery or pathological effects such as oxidative stress, proteins are modified, potentially leading to harmful protein species [4] , [5] , [6] , [7] . Therefore, to better understand disease-related proteomes on a functional level, tissue proteome must be analyzed with respect to protein species [8] , [9] , [10] . In the past decade, significant progress has been made in the field of proteomics that have now made protein species accessible to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among the identified proteins, several proteins (Fig. 2) were identified in more than one spot, we speculate that these proteins may be proteolytically or environmentally processed, modified, and/or transported to organelles or outside the cell, spliced, or degraded [18,36]. Interestingly, Thiede et al [37] found that more than 50% of the spots investigated contained more than one protein.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, within this section, we will mention some papers included in the proteinomics category. Proteomics through simple protein extracts’ preparation and a combination of chemical analysis and data documentation offers the possibility for protein speciation discourse, as reviewed by Jungblut . The analysis of different gene products (splicing variants, PTMs), allelic variants, and isoforms (it is curious to note how these terms are used in the literature in a rather confused way and sometimes as synonymous) is of great relevance for biological knowledge, and this thought requires keeping our mind away from the high‐throughput concept.…”
Section: Proteomics Areas: Descriptive Comparative Subcellular Ptmmentioning
confidence: 99%